CTCF, YB-1, c-myc, and p53 expressions of primary human hypertrophic scar and normal fibroblast skin cells in response to novel chitosan derivatives sheet - Abdull Rasad, Mohammad Syaiful Bahari; Halim, Ahmad Sukari; Hashim, Kamaruddin; Abdul Rashid, Ahmad Hazri; Lim, Chin Keong; Shamsuddin, Shaharum (Elsevier, 2008)
The primary human hypertrophic scar and normal skin fibroblasts were successfully established and identified by heat shock protein 47 and fibroblast surface protein markers. However, different patterns of protein expressions were found in cultured fibroblasts from hypertrophic scar and in normal fibroblast skin cells after treatment with the chitosan derivatives sheet. The CTCF protein was up-regulated in fibroblast hypertrophic scar on treatment with chitosan derivatives. In contrast, the amount of CTCF protein was found unchanged in normal skin fibroblasts both treated and untreated. The YB-1 protein was expressed almost similarly in normal and hypertrophic scar when treated with chitosan but the expression differed when untreated. The c-myc and p53 proteins were expressed in fibroblast hypertrophic scar followed by up-regulation after treatment with chitosan derivatives. The c-myc and p53 expressions were not detected in normal fibroblasts neither untreated nor treated. The CTCF, YB-1, c-myc, and p53 proteins acted in different manners in human hypertrophic scar and normal fibroblast skin cells. The novel chitosan derivatives sheet in this study may play roles in the control of cell growth and proliferation of human hypertrophic scar and normal fibroblast skin cells. The mechanisms underlying expression of these protein factors remain unclear, and further studies are still undergoing in our laboratory.